Pendidikan Multikultural Sebagai Upaya Mewujudkan Perdamaian di Indonesia - Selamat , Shelomita (Perspektif, 2009)
This essay deals with the issue of multiculturality as a social reality and the need to implement a multicultural education to deepen the social knowledge of Indonesia and the Indonesians. The process of globalization has been invading almost all aspect of human life, which force ordinary Indonesians to come to terms with this global movement. The notion of diversity is very strong in Indonesia and eventually considered as an internal power to deal with the diversified society. However, not every Indonesian seems to understand and live this variety as a blessing. Many even consider it as a destructive factor, a lot of social unrests in Indonesia recently were actually caused by this lack of understanding. Therefore, the author suggests that a multicultural education is very crucial and urgently needed. The national constitution and other regulations are highlighted as the legal basis of the proposed education. Meanwhile, the implementation of this kind of education needs cooperation between all social elements in Indonesia.